Microseismic characteristics of rockburst development in deep TBM tunnels with alternating soft–hard strata and application to rockburst warning: A case study of the Neelum–Jhelum hydropower project. (April 2022) - Feng, Guang-Liang; Chen, Bing-Rui; Xiao, Ya-Xun; Jiang, Quan; Li, Peng-Xiang; Zheng, Hong; Zhang, Wei
Highlights: New temporal evolution laws of microseismicity in rockburst were found. New rockmass fracturing mechanism in rockburst development process was revealed. Thresholds for six microseismic parameters used to warn of rockbursts were found. Abstract: The rockbursts that occur when tunneling through deep, hard rock can result in serious harm to workers, mechanical damage, delays, and economic losses. As a result, obtaining a warning of impending rockburst remains a challenge in rock engineering around the world. Unfortunately, the rockbursts that occur in deep tunnels with alternating soft–hard strata have development laws and mechanisms that are unclear and so are particularly difficult to predict. This paper focuses on the characteristics of the microseismicity occurring in deep tunnels constructed within alternating soft–hard strata and using the data to warn of rockburst occurrence. The study uses the Neelum–Jhelum hydropower project in Pakistan (tunnels with a maximum burial depth of 1, 890 m) as an engineering background. The temporal evolution of the microseismicity and the fracturing mechanism involved in the rockburst development process in alternating soft–hard strata were thus revealed. Thresholds for six microseismic (MS) parameters that can be used to warn of rockbursts of different intensities in different lithologies were thus found based on 58 recorded cases (recorded during a month-long period of MS monitoring). These thresholds were subsequently used (together with MS monitoring) to warn of rockbursts of a certain intensity in the corresponding lithology during the excavation of subsequent tunnels. The warning results obtained agree with the actual situation when the right thresholds for the corresponding lithologies were used. The characteristic values of the six MS parameters used for rockburst warning in different lithologies were also discussed. Our results provide a useful reference for understanding and warning of rockbursts in deep tunnels in rockmasses with similarly complex lithologies.